Sectarianism in Medieval India Śaiva, Vaiṣṇava, and syncretistic temple architecture in Karnataka - Banerji, Naseem Ahmed (Lanham Boulder New York London Lexington Books, 2019)
History of the Hoysaḷas of Karnataka -- Hoysaḷa temples, Śaivism, Vaiśnaivism and syncretism in Karnataka -- Vaiśnaivism and Sri Vaiśnava temples in Karnataka -- Śaiva sects, Viraśnaivism, and Śiva temples in Karnataka -- Syncretism and syncretistic temples in Karnataka.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Architecture, Hoysala -- India -- Karnataka; Temples -- India -- Karnataka; Hindu temples -- India -- Karnataka; Syncretism (Religion) -- India -- Karnataka